POLITICAL REALISM IN INTERNATIONAL RELATIONS: CONCEPTION AND MISCONCEPTIONS AFTER THE COLD WAR - PETRAITIS, JAUNIUS (Politologija, 2012)
Political realism is the major theoretic tradition in IR. But in contrast to the ever-growing variety of realist theories, one meets growing difficulties while trying to define the realistic approach to international politics. Contemporary theorizing in the name of “realism” marks the retreat from the basic assumptions inherent to the original tradition. This process has its immanent logic and important implications, and therefore must be analysed on its own terms.The task of this paper is to reveal the relation between the core principles of the original tradition of realism and new theories of realism after the Cold War. In the first part, the works of historically most influential classical realists are examined. Careful analysis of the main descriptive and prescriptive elements in the theories of Thucydides, Machiavelli and Hobbes enables to reveal three common descriptive principles: (I) the object of realism is politics – the never-ending and diversiform struggle for power, rooted in man’s will to power. (II) Political agents behave under Athenian thesis: power boosts their necessity to dominate. (III) Political outcomes are hardly predictable and eventually develop under the scenario of tragedy. The principles of pure realism deny the worth of abstract prescriptive reasoning. In the XXth century, these same principles were perfectly reflected in theories of Carr and Morgenthau. They both restored the old tradition and made it relevant in the age of “total” wars and nuclear weapons.In the second part, misconceptions of realism after the Cold War are analysed. It is shown that the shifts in content of contemporary realist theories are path-dependent and rooted in “Waltz paradox”. The paradox led to three different modes of realist enterprise: (i) conservative reaction; (ii) “middle way”; and (iii) radical reaction. These stages purport the gradually increasing deviation from the original descriptive principles of realism. Conservative reaction is based on a false assumption that states can follow rational winning strategies. Middle-way “realists” (mis)treat the political struggle for power only as an outgrowth of specific circumstances. More and more of them follow the liberal agenda, trying to find and neutralise the “irrational factors”, and thereby secure the rational (universally acceptable) political outcomes. Finally, radical reaction means reconstruction of realism as an entirely prescriptive discourse and moral guidelines for peaceful accommodation and liberal political order. The implications of these theoretical changes are exemplitied by discussing standard “realistic” explanations of US foreign policy after the Cold War. It is shown that none of today’s “realist” approaches is realistic enough to grasp the operation of the principles once known to realism. The findings of this research challenge the false truths about the relation between political realism, scientific IR enterprise and political practice.